2016
DOI: 10.3892/ijo.2016.3429
|View full text |Cite
|
Sign up to set email alerts
|

Selection of optimal chelator improves the contrast of GRPR imaging using bombesin analogue RM26

Abstract: Bombesin (BN) analogs bind with high affinity to gastrin-releasing peptide receptors (GRPRs) that are up-regulated in prostate cancer and can be used for the visualization of prostate cancer. The aim of this study was to investigate the influence of radionuclide-chelator complexes on the biodistribution pattern of the 111In-labeled bombesin antagonist PEG2-D-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH2 (PEG2-RM26) and to identify an optimal construct for SPECT imaging. A series of RM26 analogs N-terminally conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 29 publications
7
50
0
Order By: Relevance
“…In vitro binding specificity, cellular processing and kinetics of binding to and dissociation from living cells were evaluated using PC‐3 cells as previously described …”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…In vitro binding specificity, cellular processing and kinetics of binding to and dissociation from living cells were evaluated using PC‐3 cells as previously described …”
Section: Methodsmentioning
confidence: 94%
“…In the present work, we have modified the same GRPR‐antagonist RM26 by coupling tri‐ and tetra‐aza macrocyclic chelators to its N‐terminus via a PEG 2 ‐linker and investigated the respective 177 Lu‐labeled radiopeptides for their efficacy in GRPR‐targeted radiotherapy of prostate cancer in preclinical models. Previous studies have revealed a pronounced effect of the radiometal‐chelate on the biodistribution of RM26 in mice . Based on the newly acquired in vitro and in vivo data we have concluded that the tetra‐aza chelators DOTAGA and DOTA resulted in 177 Lu‐radioligands with the most suitable properties for TRT, showing a significantly higher tumor uptake compared to the NODAGA‐carrying radioligand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Recently, a nine-amino-acid analog of nonapeptide BBN 6–14 , d -Phe–Gln–Trp–Ala–Val–Gly–His–Sta–Leu–NH 2 (RM26) has been developed as an antagonist against GRPR and has been applied actively in preclinical studies. 2932 Based on these observations, both BBN 7–14 and RM26 are considered high-quality candidates for further clinical translation.…”
Section: Introductionmentioning
confidence: 99%